Emosi dan Penggunaan Warna Dominan Pada Kegiatan Mewarnai Anak Usia Dini - Pratiwi, Putu Yudari; Budisetyani, I Gusti Ayu Putu Wulan (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
This study aims to determine the emotion influence towards use of the dominant color on early childhood coloring activities and also see the influence of positive and negative emotions toward the dominant color that used. Emotions are a condition that involves physiological, psychological, and feelings to act, because of the stimulus received by the senses, will be response, and processed. Emotions can be divided into positive emotions consist of happiness, excitement, also surprise and negative emotions consist of anger, sadness, fear, and disgust. Colors can manifest emotions that felt by someone. Bright color associated with positive emotions, and the dark color associated with negative emotions. Dominant color is color that most widely used in one image area. To count the area of the color is using grid technique or square method. This study use quasi experimental design with treatment by subject. The sampling was 30 students from Tunas Mekar Sari Kindergarten that taken by purposive sampling technique. The data analysis methods are using Crosstabs function, Chi-Square Test, and Coefficient Contingency C. Data analysis and study result find there are three hypotheses received, those are the strong emotion influence towards use of the dominant color on early childhood coloring activities, the strong positive emotion influence towards use of the bright dominant color, also the very strong negative emotion influence towards use of the dark dominant color. Keywords: turnover intention, psychological contract violation, type A personality, bank employees